Lhasa : streets with memories - Barnett, Robert, 1953- (Asia perspectives., 2006)
There are many Lhasas. One is a grid of uniform boulevards lined with plush hotels, all-night bars, and blue-glass-fronted offices. Another is a warren of alleyways that surround a seventh-century temple built to pin down a supine demoness. A web of Stalinist, rectangular blocks houses the new nomenklatura. Crumbling mansions, once home to noble ministers, famous lovers, nationalist spies, and covert revolutionaries, now serve as shopping malls and faux-antique hotels. Each embodiment of the city partakes of the others' memories, whispered across time and along the city.